Formulasi pot organik berbasis bahan pembenah tanah untuk penggunaan di lahan gambut - Tamin, Rike Puspitasari; Hardiyanti, Rizky Ayu; Handayani, Rajjitha; Rif’atunidaudina, Ria; Rumondang, Jenny (Proceedings Academic Universitas Jambi, 2025)
The use of polybags in plant nurseries has negative environmental impacts due to their non-biodegradable nature and potential contribution to plastic pollution. This study aims to develop organic pots as an alternative to polybags, which also function as soil amendments for peatlands. The organic pots were formulated using a combination of organic and inorganic materials, including egg trays, maggot compost, cocopeat, and dolomite. Three formulations were tested with the following compositions: (1) 50% egg trays, 40% maggot compost, 5% cocopeat, and 5% dolomite; (2) 50% egg trays, 35% maggot compost, 10% cocopeat, and 5% dolomite; and (3) 50% egg trays, 30% maggot compost, 15% cocopeat, and 5% dolomite. The pots were molded using a manual tool and sun-dried. Maggot compost was used due to its high content of macro and micronutrients, as well as its alkaline pH, which helps neutralize the acidity of peat soils. The results showed that the organic pots had good physical structure, were biodegradable, and had the potential to improve seedling growth in peatland environments. This innovation offers an environmentally friendly solution for nursery management and reducing plastic waste in the forestry sector.